Nugent (2019) - Boundaries, Communities, and State-Making in West Africa. The Centrality of the Margins - Rey, Matthieu (Revue d’histoire contemporaine de l’Afrique, 2024)
Recension : Paul Nugent, Boundaries, Communities, and State-Making in West Africa. The Centrality of the Margins, Cambridge, Cambridge University Press, 2019, 610 p.